Breaking the habit of being yourself : how to lose your mind and create a new one - Dispenza, Joe, 1962- (Hay House, 2012)
Argues that all human beings have the power within them to overcome predisposed beliefs and habits to make significant changes in one's life, and provides step-by-step tools to make such changes using understandings between science and spirituality.